Ceropales pallida sp. nov. (Hymenoptera, Pompilidae, Ceropalinae) described from northern Europe - Ødegaard, Frode; Abenius, Johan; Paukkunen, Juho (Zootaxa, 2022)
A new pompilid wasp, Ceropales pallida sp. nov., is described, illustrated and distinguished from its close relative Ceropales maculata. The new species is supported by evidence from morphological characters as well as DNA barcoding. The type specimens were collected at several localities in southern Norway, Sweden and Finland.